Odpowiedzi

2010-01-05T21:03:25+01:00
2)

5(2x-y)=8x+4
3x+1= y+7 /-7


5(2x-y)=8x+4
3x-6=y

5[2x-(3x-6)]=8x+4
3x-6=y

5[2x-3x+6)]=8x+4
3x-6=y

10x-15x+30=8x+4
3x-6=y

26=13x
3x-6=y

2=x
0=y



2010-01-05T21:12:14+01:00
½ n - 2y = -5/*(-6)
3n - ½ y = 9/2
{-3n+12y=30
{3n-0,5y=4,5
~~~~~~~~~~~~
___11,5y=34,5/:11,5
______y=3
¹/₂n-2y=-5
0,5n-2*3=-5
0,5n-6=-5
0,5n=-5+6
0,5n=1/:0,5
n=2

5(2x-y)=8x+4
3x+1= y+7
{10x-5y=8x+4
{3x+1=y+7

{10x-8x-5y=4
{3x-y=7-1

{2x-5y=4
{3x-y=6/(-5)

{2x-5y=4
{-15x+5y=-30
~~~~~~~~~~~~
__-13x=-26/:(-13)
_____x=2
2x-5y=4
2*2-5y=4
4-5y=4
-5y=4-4
-5y=0/:(-5)
y=0